Kepatuhan Perusahaan Modal Dalam Negeri (PMDN) Dalam Pelaksanaan Peraturan Perundang-Undangan (Studi di PT Yumeida Utama) - Ismed Batubara; Yeltriana Yeltriana; M. Arif Hadian (Jurnal Ilmiah Penegakan Hukum, 2026)
This study aims to analyze the level of compliance of Domestic Investment Companies (PMDN) with applicable laws and regulations, particularly regarding the obligation to obtain a Business Identification Number (NIB) and to establish a Collective Labor Agreement (CLA) as an instrument for protecting workers’ rights. This research employs a normative juridical method with a descriptive approach based on secondary data. The findings indicate that the existence of the NIB, as part of business licensing reform, provides administrative convenience for companies; however, it must be aligned with the fulfillment of industrial relations aspects through the CLA. The case study of PT Yumeida Utama shows that the company has fulfilled juridical compliance by obtaining an NIB and sociological compliance through the establishment of a CLA with the labor union. Nevertheless, several aspects still require improvement, such as provisions on bonuses and mechanisms for resolving industrial relations disputes. This study concludes that the synchronization between administrative obligations and democratic industrial relations practices is essential to ensure corporate compliance with applicable laws.